In Vivo TLR9 Inhibition Attenuates CpG-Induced Myocardial Dysfunction - O. Boehm; P. Markowski; M. van der Giet; V. Gielen; A. Kokalova; C. Brill; A. Hoeft; G. Baumgarten; R. Meyer; P. Knuefermann (Hindawi Limited, 2013)
The involvement of toll-like receptor 9 (TLR9), a receptor for bacterial DNA, in septic cardiac depression has not been clarified in vivo. Thus, the aim of the study was to test possible TLR9 inhibitors (H154-thioate, IRS954-thioate, and chloroquine) for their ability to protect the cardiovascular system in a murine model of CpG oligodeoxynucleotide- (ODN-) dependent systemic inflammation. Sepsis was induced by i.p. application of the TLR9 agonist 1668-thioate in C57BL/6 wild type (WT) and TLR9-deficient (TLR9-D) mice. Thirty minutes after stimulation TLR9 antagonists were applied i.v. Survival was monitored up to 18 h after stimulation. Cardiac mRNA expression of inflammatory mediators was analyzed 2 h and 6 h after stimulation with 1668-thioate and hemodynamic parameters were monitored at the later time point. Stimulation with 1668-thioate induced a severe sepsis-like state with significant drop of body temperature and significantly increased mortality in WT animals. Additionally, there was a time-dependent increase of inflammatory mediators in the heart accompanied by development of septic heart failure. These effects were not observed in TLR9-D mice. Inhibition of TLR9 by the suppressive ODN H154-thioate significantly ameliorated cardiac inflammation, preserved cardiac function, and improved survival. This suppressive ODN was the most efficient inhibitor of the tested substances.